174k views
22 votes
Create an equation with one solution of x = −5.
9x − (x − 3) = 2x − (__ + x)
7.4 #7

1 Answer

10 votes

Answer:

9x-(x-3) = 2x - (-5 + x)

Explanation:

Let's say blank is the variable a.

9x-(x-3) = 2x - (a + x)

Simplify the equation:

9x-(x-3) = 2x - ( a + x)

9x - x + 3 = 2x - a - x

8x + 3 = x - a

7x + 3 = -a

a = -7x - 3

Plug in -5 for x:

a = -7*-5 - 3 = 35 - 3 = 32

a = 32 so the equation with one solution of x = -5 would

9x-(x-3) = 2x - (-5 + x)

User Bofredo
by
4.7k points